Pengembangan Media Pembelajaran Berbasis Android pada Mata Kuliah Keperawatan Medikal Bedah III - Yosi Oktarina; Sri Mulyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Technological developments have led to smartphones becoming one of the media that can be used in learning. The use of smartphones as a learning medium is commonly referred to as mobile learning. The operating system that is widely used by smartphones in Indonesia is Android which uses an open source system. This encourages the development of a number of android-based learning applications. This study aims to develop an android-based learning application, especially in the Medical Surgical Nursing III course which contains a number of materials, quizzes, and learning video. The design used in this research is research and design. The stages that are passed include field studies, initial planning, initial product development, validation of media and materials experts, limited trials, revisions, and large-scale trials. The testing phase at the beginning of the product was carried out on one media expert, one material expert, and 25 students. Assessments from media experts, material experts, and students were carried out using a questionnaire. Furthermore, the data were analyzed using percentages. At the initial stage, the assessment from material experts got a score of 92.10%, the initial assessment from media experts got a score of 83.03%, and student responses with a score of 81.89%. Furthermore, based on input from media experts and student responses, a number of revisions were made and retested to media experts and 40 students. The results obtained from media experts are 83.51% and the results obtained based on student responses are 84.25%. The results showed that this application was included in the very good/decent category. It is hoped that this application can be used as one of the learning media, especially in the Medical Surgical Nursing III course.